In Silico Study on FtsZ as a Novel Target for Antibacterial Activity (International Journal of Food and Nutritional Sciences, 2022)
In silico molecular docking isusedto predict the binding affinity of a ligand towards the receptor. In this study, the bioactive compounds of Carissa carandas plant extractare used as a ligand of the FtsZ receptor. FtsZ is a protein find the bacteria, which is responsible for cell division.Molecular docking is conducted to analyze the potential anti-bacterial compounds found in the Carissa carandas. The bioactive constituents of Carissa carandas plant extract have been identified through gas chromatography MS analysis. The identified compounds include alkaloids, flavonoids, saponins, and phenolic acids. The pharmacological and nutraceutical profile of Carissa species, particularly Carissa carandas, has been examined in several areas of research. These studies have identified various bioactive constituents that is a potential inhibitor of FtsZ. The bioactive compounds 4-Bromobenzenesulfono-2-napthamide, 2,6-Dimethyl-7-octyl-1,2,3,4-tetrahydronic and Acetamide found as the best hit of the target, which ranges binding energy between (-9.06 to -6.42 kcal/mol).Thus,the identified inhibitor could serve as a potential inhibitor of FtsZ, further in vitro and in vivo studies need to validate these results.